In Vitro Antimicrobial Activity of the Decontaminant HybenX(®) Compared to Chlorhexidine and Sodium Hypochlorite against Common Bacterial and Yeast Pathogens - Antonelli, Alberto (Antibiotics (Basel), 2019)
The recent increase in infections mediated by drug-resistant bacterial and fungal pathogens underlines the urgent need for novel antimicrobial compounds. In this study, the antimicrobial activity (inhibitory and cidal) of HybenX(®), a novel dessicating agent, in comparison with commonly used sodium hypochlorite and chlorhexidine, against a collection of bacterial and yeast strains representative of the most common human pathogenic species was evaluated. The minimal inhibitory, bactericidal, and fungicidal concentrations (MIC, MBC, and MFC, respectively) of the three different antimicrobial agents were evaluated by broth microdilution assays, followed by subculturing of suitable dilutions. HybenX(®) was active against 26 reference strains representative of staphylococci, enterococci, Enterobacterales, Gram-negative nonfermenters, and yeasts, although at higher concentrations than sodium hypochlorite and chlorhexidine. HybenX(®) MICs were 0.39% for bacteria (with MBCs ranging between 0.39% and 0.78%), and 0.1–0.78% for yeasts (with MFCs ranging between 0.78% and 1.6%). HybenX(®) exhibited potent inhibitory and cidal activity at low concentrations against several bacterial and yeast pathogens. These findings suggest that HybenX(®) could be of interest for the treatment of parodontal and endodontic infections and also for bacterial and fungal infections of other mucous membranes and skin as an alternative to sodium hypochlorite and chlorhexidine.